A Bolsa de Bielsa e Outras Histórias para Espreitar o Futuro - Louçã, João Carlos (Trabalhos de Antropologia e Etnologia, 2020)
By questioning the Enlightenment on its premise of the existence of a Universal Reason that Eric Wolf tackled in detail (1999) or of what Sahlins called the “Western illusion of human nature” (2011), Anthropology may in future have a significant field for thinking the world we live in. In the capitalism of a universal vocation, that neoliberalism has managed to impose, the naturalization of the ideas that justify itself is part of a hegemonic current that transforms neoliberal ideology into a condition of human nature. Cultures of resistance are thus a condition for thinking counter-hegemonic practices, or simply social realities that still escape the expropriation of common goods, the privatization of the future as a space of desire and collective imagination. In Bloch's (1982) praxis of concrete utopia, there may lie the horizon of the expectation that what is to come already exists.. Is there a bigger challenge for the social sciences?